Combinations of Tense Forms in Folk Lyric Poetry - Ćišić, Alma (Stylistyka, 2021)
The main task of this paper has been to investigate the ways of combining tense forms in folk lyric poetry. The concept of folk lyric poetry in this case refers to the oriental-style love-song, the folk love song which was created with the advent of the eastem Islamie culture into the Slavic south, mostly among the part of the population which accepted the Islam. In terms of context, oriental-style love-songs are a shorter kind of songs, of about ten verse lines on average. Even though the texts in ąuestion are fairly short, they include multiple combinations of the tense forms employed. That is primarily due to the way of presenting their verbal content. The author has proved that the present tense form is the most frequent in this poetry. Why that is so and how its main function is realised are the issues treated in this paper. The author proves there is no oriental-style love-song belon- ging to verbless poetry, that all the songs were composed with the use of two, or usually morę tense forms. The most frequent are the combinations of the present and past tenses, the latter most often expressed by the perfect tense and the aorist. Morę rarely the futurę tense form is involved too.